G2 parametric curve and surface fitting using beta-spline / Normi Abdul Hadi - Abdul Hadi, Normi (Institute of Graduate Studies, UiTM, 2015)
Advancement of the imaging technology nowadays demands sophisticated method to represent the captured image in the form of curves and surfaces. However, the challenge in curve and surface fitting techniques is the smoothness and accurateness of the result and the complexity of the techniques. Therefore, the primary goal of this research is to develop new curve and surface fitting techniques using beta-spline which has G2 continuity, high accuracy and less number of computations. This is due to the properties of cubic beta-spline itself with G2 conditions, and located close to the control polygon. Additionally, beta-spline can be controlled in three ways using control points, shape parameters and weights…